The relevance of al-Qabisy’s ideas on Qur’anic education among children - Md Sawari, Siti Salwa; Mustapha, Nurul Izzah; Awang Mat, Muhamad Zahiri; Omar, Intan Marfarrina (Journal of Islamic, Social, Economics and Development (JISED), 2019)
Islam has a great significance to education. In Islam, Qur’anic education is view as an important element in educating the children. Without it, the future of Muslim generation will be jeopardised. This paper intends to provide an analysis of al-Qabisy’s ideas and the implications of his ideas on enhancing the Qur’anic teaching among children. A content analysis method was used to obtain the research objectives. This paper has discovered the relevance of Al’Qabisy ideas on eight components of Qur’anic education; learner's level, educators, intention, educator’s responsibility, syllabus, schedule, learning stages, and assessment. The entire components presented in his book are significantly beneficial in enhancing the Qur’anic teaching among children. It is hoped that the ideas presented in this article will be helpful in upgrading the level of the Qur’anic teaching among children.